A rapid and cost‐effective method based on dispersive liquid‐liquid microextraction coupled to injection port silylation‐gas chromatography‐mass spectrometry for determination of morphine in illicit opium. Issue 7 (20th November 2020) - Jain, Rajeev; Singh, Meenu; Kumari, Aparna; Tripathi, Rohitshva Mani
Abstract: A simple, rapid, cost‐effective and environment friendly analytical method based on dispersive liquid‐liquid microextraction (DLLME) coupled to injection port silylation (IPS)–gas chromatography‐mass spectrometry is described for the determination of morphine in illicit opium samples. Raw opium was dispersed in ultrapure water and 5 mL of aqueous sample was subjected to DLLME by rapidly injecting a mixture of chloroform and acetone (extraction and disperser solvent, respectively) followed by ultrasonication for 1 min and subsequent centrifugation for 3 min at 5000 rpm. The sedimented phase thus obtained was reconstituted in acetonitrile and 1 µL along with 1 µL of N, O‐Bis(trimethylsilyl)acetamide (BSA) was injected manually into GC‐MS injection port at a temperature of 250°C. The derivatization reaction was completed instantaneously inside the heated GC‐MS injection port without any side product. Various parameters associated with IPS and DLLME have been thoroughly optimized. Under the optimized conditions, the method has been found linear in the range of 5‐50 µg/mL with a correlation coefficient ( R 2 ) of 0.997. The limit of detection (LOD) and limit of quantification (LOQ) for morphine‐diTMS were found to be 1.6 and 4.8 µg/mL. The method has been successfully applied for the quantitative analysis of morphine in illicit opium samples. In conclusion, the proposed method has completely eliminated the time consuming and laborious steps of LLE and in‐vial silylation and can be routinely used for analysis of opium and other polar analytes in forensic science laboratories.